2007
DOI: 10.1007/s10863-007-9077-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in platelets and hippocampi of senescence-accelerated mice

Abstract: Senescence-accelerated mice (SAM) strains are useful models to understand the mechanisms of age-dependent degeneration. In this study, measurements of the mitochondrial membrane potential (Deltapsi(m)) of platelets and the Adenosine 5(')-triphosphate (ATP) content of hippocampi and platelets were made, and platelet mitochondria were observed in SAMP8 (faster aging mice) and SAMR1 (aging resistant control mice) at 2, 6 and 9 months of age. In addition, an Abeta-induced (Amyloid beta-protein) damage model of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…On the other hand, our results are in agreement with those authors who observed altered mitochondrial dysfunction in SAMP8 mice. For instance, Nishikawa et al (1998) detected an early stage mechanism underlying the age-associated mitochondrial dysfunction present in SAMP8 mouse brain, and Xu et al (2007) reported that platelet mitochondrial membrane potential as well as hippocampal and platelet ATP content in SAMP8 mice decreased at early age compared with SAMR1. Thus, our results support the contention that mitochondrial alterations may play a key role in the aging process.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our results are in agreement with those authors who observed altered mitochondrial dysfunction in SAMP8 mice. For instance, Nishikawa et al (1998) detected an early stage mechanism underlying the age-associated mitochondrial dysfunction present in SAMP8 mouse brain, and Xu et al (2007) reported that platelet mitochondrial membrane potential as well as hippocampal and platelet ATP content in SAMP8 mice decreased at early age compared with SAMR1. Thus, our results support the contention that mitochondrial alterations may play a key role in the aging process.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, age-related changes in levels of antioxidant enzymes, such as copper/zinc superoxide dismutase (Cu/Zn-SOD) and manganese SOD (Mn-SOD), have been found in liver and cortex of SAMP8 mice when compared with age-matched SAMR1 mice, supporting increased oxidative stress as a key mechanism involved in the aging process (37). More recently, Yew and collaborators have shown an impairment of mitochondrial functions including a decrease of COX activity, mitochondrial ATP content, and mitochondrial glutathione (GSH) level at a relatively early age in SAMP8 mice compared with SAMR1 mice (67,78). Furthermore, the biochemical consequences of aging have been investigated using proteomic analysis in the brain of SAMP8 and SAMR1 mice at presymptomatic (5-month old) and symptomatic (15-month old) stages (84), revealing differentially expressed proteins with age in both mouse strains, such as Cu/Zn-SOD.…”
Section: Mitochondrial Aging-the Beginning Of the End In Ad?mentioning
confidence: 96%
“…Furthermore, increased levels of oxidative stress markers have been detected in younger (4-week-to 5-month-old) SAMP8 mice [30][31][32][33]. Mitochondrial dysfunction has also been demonstrated in SAMP8 mice in their younger period [34][35][36], although a decrease in ATP production was observed at a relatively later period (9-18 months of age) [36,37]. Taken together, these innate subtle abnormalities in the mitochondrial respiratory chain might cause a gradual accumulation of oxidative damage in vital macromolecules in the cells, which eventually results in brain dysfunction at an older age.…”
Section: A Higher Oxidative Stress Status Is a Primary Characteristicmentioning
confidence: 99%